How successful is the Industrial Institutes, Kuwait, in reducing dependence on expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
Nowadays, no one can deny the role played by technical and vocational education in reducing the rate of youth unemployment, low rate of poverty, high wages, and livelihood for workers, particularly younger workers. Technical and vocational education is a dual type of educational system that permit students to acquire the necessary knowledge, skills, and attitudes mostly needed by industries and business. The quality of technical and vocational educations would facilitate the transformation of students from classrooms, workshops, and laboratories into real work environment. The success of technical and vocational education in achieving the its objectives would depend on the quality of management in forging a strong linkage with industries and business. The concept of working in a “black box” would not apply in technical and vocational education since industries and business are the main contributors in shaping students’ knowledge, skills, and attitudes. Kuwait, as one of the gulf states, the shortage of indigenous skilled and semi-skilled manpower in noted in essential sectors of the economy (e.g., electricity and water and the oil sector). Key figures have appreciated the significant role of technical and vocational institutions in providing essential sectors of the economy with the skilled and semi-skilled national manpower in order to reduce, to great extent, the dependence on expatriates. The Sabah Al-Salem Industrial Institute, SSII, and Shuwaikh Industrial Institute, SII, was forged between 1992-1993, by the Kuwaiti Government with the aim to equipped local manpower with the know-how and know-why that are applied in local industries and business. The research is focus on measuring the perception of a sample of heads of supervisors at the Ministry of Electricity and Water and at the oil sector towards the quality of the graduates from the Sabah Al-Salem Industrial Institute, SSII, and Shuwaikh Industrial Institute, SII. The research is based on extensive field work that encompasses a review of the related literature, interviews with a sample of heads of supervisors at the Ministry of Electricity and Water and at the oil sector to assess the quality of SSII & SII, graduates. Finally, the research will argue that unless the Sabah Al-Salem Industrial Institute, SSII, and the Shuwaikh Industrial Institute, SII, recognize and appreciate the value of building a strong linkage with local industries, its contribution in tackling the shortage of skilled and semi-skilled indigenous in essential sectors on the economy will be below the government expectations, thus continuing relaying on expatriates for years ahead.